THE INFLUENCE OF THE LEVEL OF UNEMPLOYMENT ON THE DEVELOPMENT OF ENTREPRENEURSHIP IN UKRAINE - Власенко, Ірина; Тернова, Алла (SWorldJournal, 2024)
The article shows that the drop in production and the growth of unemployment is a key risk for the functioning of the Ukrainian economy. This is due to a reduction in production, a decrease in tax revenues and the country's GDP, and an increase in budget